Does technology affect event management in Malaysia? A case study of stair climb sporting race / Fatimah Nur Mohd Redzwan, Nur Idawati Md. Enzai and Mazratul Firdaus Mohd Zin - Mahdzar, Mazlina; Muhammaddin, Mohamad Hafizam; Zulkivly Zulkepli, Zaimm Zulhazziq (2017)
This paper investigates and compares the effects of technology in event management in Malaysia, a case study of stair climb sporting race. In a multiracial society, male and female participation in sports have different in their decisions when it comes to pursue sporting events of interest. Generally, sport activities require physical strength and risk taking, thus attracting only male participation. This study is concerned with the gender differences and their experiences with the event and particularly on the use of technology. The quantitative approach has been employed to perform the statistical analysis relies on numerical evidence. The results reveal significant differences between the effects of technology and event management by gender on the stair climb race event. This study makes a significant contribution to the event management and technology's effects and adds contribution to the on going literature by comparing male and female gender. It also provides insights to the event operators in preparing strategies to tap the sporting events market.